Kinetic aspects of the Diels–Alder reaction between poly(styrene-co-furfuryl methacrylate) and bismaleimide - Goiti, Eunate; Heatley, Frank; Huglin, Malcolm B; Rego, José M (European polymer journal, 2004)
The crosslinking Diels–Alder reaction between styrene–furfuryl methacrylate copolymer samples (poly(ST-co-FM)) and bismaleimide (BM) at 25 °C in chloroform was studied by following the decay in UV absorbance of the maleimide (MI) group at 320 nm. Reaction conditions were changed by using copolymers with different mole fraction of FM, F FM, and by employing different initial molar ratios of reactants (furan group within FM and MI group within BM). Second order kinetics were obeyed. 13C NMR spectra showed that, even when all reactants had been converted to an insoluble crosslinked network, unreacted MI groups remained, presumably in the form of singly reacted pendant BM molecules. The fractions of MI groups remaining unreacted were found to be 0.49, 0.34 and 0.22 for FM:MI mole ratios in the initial mixture of 2, 1 and 0.5 respectively, when using a copolymer of F FM=0.1354. An attempt was also made to follow the kinetics of network formation by 13C NMR spectroscopy, using the peak areas for reacted and unreacted MI and FM groups, but many of the findings were subject to some uncertainty for reasons, which are discussed. However, because the peak areas were considered reliable for unreacted MI groups, the rate constant, k, was evaluated, thereby. Overall using UV and NMR the values of k lay within the interval (0.8–3.6) × 10 −5 dm 3 mol −1 s −1.